ANALISIS PENGARUH PEMILIHAN METODE AKUNTANSI TERHADAP TINGKAT UNDERPRICING SAHAM PERDANA PADA PERUSAHAAN MANUFAKTUR DAN NON MANUFAKTUR - Iis Rohayati (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
The Objective of this Research is to test influence underpricing generated by usage of accounting method at manufacturing business and non manufacturing business in Indonesian Stock Exchange. In this research used by variable is underpricing as dependen variable where Depreciation and Inventory independent variable, by enhancing ownership of share and auditor reputation as control variable. Amount of company IPO during year 1994-2008 counted 126 company and counted 79 company fulfilling criterion as sampel, 44 manufacturing business and 35 company of non manufacturing business. Sampel taken by using sampling purposive method. Some statistic test used to test examination of classic assumption, feasibility model and hypothesis. Empirically result of this research that depreciation straight line method have an effect on positive to underpricing, depreciation double declining method have an effect on negativity to underpricing, FIFO Inventory method have an effect on positive to underpricing, average inventory method have an effect on negativity to underpricing, ownership of share have an effect on negativity to underpricing and auditor reputation have an effect on positive to underpricing.